PERBANDINGAN PENEGAKAN HUKUM TERHADAP PRAKTIK KARTEL HARGA DI INDONESIA DAN AMERIKA SERIKAT: TINJAUAN ASPEK PEMBUKTIAN DAN SANKSI - Putri, Aya Devina Rifani; Kurnia, Mahendra Putra; Pribadi, Slamet (Jurnal Ilmiah Advokasi, 2025)
This study analyzes the regulation of cartel prohibition in Indonesia based on Law Number 5 of 1999 and compares it with the antitrust approach in the United States, which emphasizes the per se illegal principle. The purpose of this research is to explore the effectiveness of each system in combating cartel practices and to identify the challenges faced by the Indonesia Competition Commission (KPPU) in the national context. This study employs a normative legal method and comparative analysis of legal instruments and enforcement practices in both countries. The findings indicate that the rule of reason approach applied in Indonesia faces evidentiary difficulties and a low culture of compliance, whereas the per se illegal doctrine in the United States has proven to be more assertive in eradicating cartels through a combination of administrative and criminal sanctions. The study recommends that Indonesia consider a gradual transition toward adopting the per se illegal approach for specific types of cartels, in order to enhance enforcement effectiveness and foster a healthier competitive climate.Keywords: Law enforcement; Cartel; Competition law